Rape loot pillage: the political economy of sexual violence in armed conflict - Meger, Sara (Oxford studies in gender and international relations, 2016)
The securitization of sexual violence -- Toward a feminist political economy of sexual violence in war -- A preliminary typology of wartime sexual violence -- Sexual violence as an instrument of terror/torture -- Sexual violence as a weapon of war -- Sexual violence as an element of genocide -- The political economy of sexual violence in the DRC -- Sexual violence against men and boys in armed conflict -- From fetishization to politicization and gendered peace